2014–2015: a view from Greece. (10th December 2015) - Morgan, Catherine
Abstract : In a year when financial crisis and EU turmoil have gripped Greece and dominated international press coverage, one might be forgiven for assuming that there would be slow progress in archaeological research and heritage management. It has certainly been a tumultuous year, and heartfelt thanks are due to colleagues, especially those in the Archaeological Service, who have gone the extra mile to deliver their own work and to help others in the face of mounting pressures. In 2014 alone, the Central Archaeological Council dealt with 1, 477 cases in 42 sittings, and its 2015 target is set to exceed this. Yet as I take stock of what has been achieved in publication, fieldwork, study and public communication, I am struck by the wealth of new information available and in many forms. Individual finds, continuing research programmes and a number of landmark conferences and exhibitions have contributed to real and significant advances in knowledge. There is much to report, and even more to see on the ground for readers inspired (as we hope) to spend time in Greece.